Technologie du fait maritime chez les Kalinago des Petites Antilles aux xvie et xviie siècles - Benoît Bérard; Jean-Yves Billard; Thierry L’Etang; Guillaume Lalubie; Costantino Nicolizas; Bruno Ramstein; Emma Slayton (Journal de la Société des Américanistes)
A large set of historical documents give us descriptions of Antillean Amerindian boats. These texts constitute a continuous series from the time of first contact to sub-contemporaneous anthropological descriptions. This paper is based on extensive review of the data contained in those early Spanish, Dutch, English, and French sources and also on a review of the few direct archaeological evidences. In this way we tried to analyse not only the nature of the relationship that existed between Antillean Amerindians and the sea but also to obtain an accurate description of their different boat types. Finally we have reconstituted the building process chaîne opératoire of the kanawa, which were the boat type specifically designed and preferentially used for over-sea navigations.